Clinico-Pathological Characteristics of Penile Cancer Patients at Sanglah General Hospital Denpasar, Bali between 2013-2020 - Suharta, I Gusti Ngurah Agung Indra; Yudiana, I Wayan; Oka, Anak Agung Gde (JBN (Jurnal Bedah Nasional), 2024)
Aim: To know prevalence and clinico-pathological characteristic of penile cancer patients at Sanglah General Hospital Denpasar between 2013 until 2020 or for 7 years periode. Methods: A cross-sectional study to collect retrospective data of penile cancer patients at Sanglah Genaral Hospital from medical records between August 2013 until August 2020. Demographics data consisted of age group and patient’s origin, meanwhile histopathological data included pathological staging, histological subtype, grading, and lymphovascular invasion. Results: 96 penile cancer patients were collected for 7 years. The highest incidence was in 2020. Mean age was 57.60 ± 12.28 years old which dominantly in 60–69 years old groups. Most of patients origin from the rural area. The highest proportions were T3 stage (41,7%), N0 stage (38,5%), M0 stage (94,7%), SCC subtype (89,6%), G2 grade (71,9%), and LVI negative (65,4%). Conclusion: The prevalence of penile cancer patients are fluctuating but tended to increase since 2017. The peak incidence was in 60-69 years old group and from the rural area. Based on TNM staging system, the highest proportion was T3, N0, M0 and G2.